UMP graduand Budin moved by a surprise from noble-hearted lecturer - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 8 November 2022 – A Facebook post went viral and captured the attention and heart of many netizens when a lecturer shared his excitement in surprising his student Muhamad Syihabuddin Abdul Wahab, fondly known as ‘Budin’, to celebrate the Universiti Malaysia Pahang (UMP) 17th Convocation Ceremony recently.